ANALISIS HUKUM PENGUASAAN TANAH BEKAS HGU OLEH PETANI PENGGARAP (STUDI PENGUASAAN TANAH BEKAS HGU PT.PERKEBUNAN NUSANTARA II OLEH KELOMPOK TANI BERJUANG MURNI DESA MARINDAL 1) - Saddam Hussein; Syafruddin Kalo; Hasim Purba; Edy Ikhsan (USU LAW JOURNAL, 2018)
ABSTRACT The polemic against access to the distribution of land since the colonial era until now has not found the light of many already the regulations of the Constitution and the MPR TAP until the following rules governing the ownership, designation and management of land. Sometimes the law looks like it is unfair to the peasants, but if it is to be said the law has been arranged in such a way as to ensure legal certainty and legal justice. The problem lies in the state institutions that do not quickly see the problem of land as the case of the former HGU PTPN II area which in fact the land must be linked to the implementation of Landreform in Indonesia.The rights to work on the land have not been clearly written like other rights in the Basic Agrarian Law, but can be interpreted and found in some UUPA Articles and in other laws related to the implementation of land reform, on State lands designated as The object of redistribution is first given "permission to work" before being increased its right to property rights. The lands that are the object of redistribution in the framework of land reform implementation, as specified in PP no. 224 of 1961 which amended by PP 41 of 1964. After the lands are designated as objects of redistribution, the Bupati as the official in charge of implementing land reform in the regency area issues the license to work on the redistribution recipients as determined by Keppres 55/1980 and Kep.MDN No.38 1981. Permit to apply is granted For a maximum period of 2 (two) years and to tenants shall be obliged to pay to the State equal to one third of the harvest or money worth of it. The chronology of the struggle of this purely struggling peasant group began in 2000 which after expiration of the period of the Right to Use Business PT. Perkebunan Nusantara II Marendal Garden I community ran the land by cultivating to increase the daily necessities of life due to the monetary crisis that befell their family life at that time, so with such conditions that Village Head Marendal 1 (Surya Ratsin) and Pataksak Head (Nasbul Siregar) issued and issued Land Acquisition Letter (SKT) on former Land Usage (HGU) land of PTPN II Marendal Village 1, for example: SKT number 592.1 / 4086-3- issued by Village Head and based on information Submitted by the Head of Village and Camat that a part of the above mentioned land will be issued Certificate (SKT) from the sub-district number 592.1 / 408603. Keywords        : Hak Guna Usaha, Garapan Rights Society , PTPN II